Analysis of Learning Difficulties of Students in Biology Subjects in Junior High School - Leo, Marince Inforsalina (Jurnal Pijar Mipa, 2025)
Students' learning difficulties are generally influenced by two aspects, namely internal factors and external factors. Internal factors involve a lack of interest in learning, a lack of natural talent in a particular field, and health problems that can hinder the learning process. This study aims to analyze the learning difficulties of eighth-grade students in biology at Satap Penmina Junior High School. Data analysis was conducted using descriptive qualitative methods, with data obtained from student learning outcomes and questionnaire responses. The analysis identified factors contributing to learning difficulties among students at SMP Satap Penmina, including both internal and external factors. Internal factors included health issues, self-readiness, and difficulties, while external factors included school facilities and family support. Based on the research findings, it was concluded that the factors causing students' difficulties in learning biology are internal factors such as health (32%), self-readiness (30%), and difficulties (32%) (low category). External factors include family (32%) in the low category and school (35%) in the moderate category.